The public reallocation of resources across age: A comparison of Austria and Sweden - Bernhard Hammer; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2012)
There is a strong interdependency between public transfers and the shape of the economic life-cycle. Austria and Sweden are very similar economies in terms of production, income and the size of the public sector. There are however remarkable differences in the design of public transfers, their distribution over age-groups and consequently in the shape of the average economic life-cycle: One of the most remarkable differences is the earlier labour force exit age in Austria. The period of active labour force participation is consequently more compressed in Austria, leading to higher contributions to the public transfer system for the age-groups 20-45 and to a higher share of public transfers directed to the elderly. Using economic dependency ratios we show that the sustainability of the public transfer system depends less on its size than on its design: The Swedish system collects the contributions from a wider range of age-groups, transfers a smaller share to the elderly and provides more support to younger generations, supporting them to invest in own children. These characteristics have a positive effect on the sustainability of the Swedish system: Although in Sweden there is a larger share of the population in the age-group 60+, the total economic dependency of the elderly is lower.
Keywords: 330